Estimativa de evapotranspiração de referência na região de Rio Paranaíba-MG - de Oliveira, Vinicius Mendes Rodrigues; Dantas, Geffson de Figueredo [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Dalri, Alexandre Barcelos [UNESP]; dos Santos, Miquéias Gomes [UNESP]; Fischer Filho, João Alberto [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
The water depth to be applied is a factor of utmost importance for the success of irrigated crops. The objective of this study was to evaluate the correlation of ETo estimate methods proposed by Hargreaves and Samani, Camargo and Jensen-Haise (JH) and the standard PenmanMonteith-FAO (PM-FAO) method, by setting up regional adjustment coefficients for the region of Rio Parnaiba, MG. Climate data collected at the meteorological station in Rio Paranaiba, MG (19°09'47'' S; 46°16'36´´O) were used from July 1, 2011 to June 30, 2013. The performance index (c), accuracy index (d), standard error of estimate (SEE) and correlation index (r) were used for comparisons. Considering the methods to estimate evapotranspiration, the JH method presented the highest correlation with the standard method (PM-FAO), r2 of 89%. According to the results, the JH equation for ETo calculation in the region of Paranaíba, MG is recommended, as this model presented the best evapotranspiration estimate. Correcting the evapotranspiration data, all study equations may be used to estimate evapotranspiration approaching the PM-FAO method.
Estimate of reference evapotranspiration in the Rio Paranaíba region - MG
Keywords: Empirical equations; Hargreaves and Samani; Jansen-Haise; Penman-Monteith